PELATIHAN WEBSITE E-COMMERCE UNTUK PENINGKATAN PENDAPATAN BUDIDAYA AGLONEMA PADA HEND'Z FLORIST AGLONEMA SAWANGAN DEPOK - Sunarti, Sunarti; Wulandari, Dewi Ayu Nur; Kuspriyono, Taat; Salvana, Alsa Diva; Nisa, Navira Aura; Anwar, Syafina; Fatiha, Syalysia Luna; Rahmawati, Winda (Jurnal Terapan Abdimas, 2022)
Abstract. Aglonema is an ornamental plant that currently has a lot of fans. Aglonema has economic value. There are so many aglonemas in Hend'z Florist Aglonema Sawangan Depok. There are problems faced by Hend'z Florist Aglonema in his cultivation in marketing using only social media such as youtube and conventional word of mouth. Answering the problems of the service team making information technology based on e-commerce websites. The purpose of this activity is to utilize science and technology (IPTEK) for aglonema cultivation business strategy for the creation of welfare based on e-commerce websites. The stages of implementing this service are carried out by providing socialization, training, mentoring, evaluation, simulation, monitoring, and sustainability. The method used is learning by doing, for this method begins with a direct field review to monitor and evaluate the results of the training that has been carried out. The mentoring process in this service includes socialization, training, evaluation, simulation, monitoring, and evaluation. From the results of the assistance carried out by partners, they were able to apply the use of technology by 88%, helping to increase knowledge and skills in the field of digital marketing by 85% and being able to increase the partners' income. To ensure the success of the implementation of community service, the evaluation stage will be carried out at each stage of program development. Abstrak. Aglonema merupakan tanaman hias saat ini banyak sekali peminatnya. Aglonema memiliki value ekonomis. Banyak sekali aglonema ada pada Hend'z Florist Aglonema Sawangan Depok. Ada permasalahan yang dihadapi Hend'z Florist Aglonema pada budidayanya dalam pemasaran hanya menggunakan media sosial seperti youtube dan konvensiaonal dari mulut ke mulut. Menjawab permasalahan tim pengabdi membuat teknologi informasi berbasis website e-commerce. Tujuan kegiatan ini memanfaatkan ilmu pengetahuan dan teknologi (IPTEK) untuk strategi bisnis budidaya aglonema demi terciptanya kesejahteraan berbasis website e-commerce. Tahapan-tahapan terlaksananya pengabdian ini dilakukan dengan pemberian sosialisasi, pelatihan, pendampingan, evaluasi, simulasi, monitoring dan berkelanjutan. Metode yang digunakan ialah learning by doing, untuk metode ini diawali peninjauan langsung kelapangan hingga monitoring dan evaluasi dari hasil pelatihan yang sudah terlaksana. Proses pendampingan dalam pengabdian ini seperti sosialisasi, pelatihan, evaluasi, simulasi, monitoring dan evaluasi. Dari hasil pendampingan yang dilakukan mitra mampu menerapkan penggunaan teknologi sebesar 88%, membantu meningkatkan pengetahuan dan keterampilan dibidang digital marketing sebesar 85% dan dapat menaikkan pendapatan mitra tersebut. Untuk memastikan keberhasilan pelaksanaan pengabdian masyarakat, maka tahapan evaluasi akan dilakukan pada setiap tahap pengembangan program.